An asymmetric acetate-Mannich reaction of chiral isatin derived ketimines and its applications. Issue 43 (30th October 2017) - Hajra, Saumen; Bhosale, Suhas Shivajirao; Hazra, Atanu
Abstract : A highly efficient TMSOTf-mediated asymmetric acetate-Mannich reaction of chiral isatin derived ketimines and S -phenyl thioacetate was developed to afford the direct synthesis of indole-based β 3, 3 -amino acid thioester with excellent selectivity (dr > 98 : 2). Syntheses of (+)-AG-041R and 3-aminopyrroloindoline have been accomplished utilizing the method. Abstract : A highly efficient TMSOTf-mediated asymmetric acetate-Mannich reaction of isatin derived tert -butylsulfinyl ketimines and S -phenyl thioacetate was developed to afford the direct synthesis of indole-based β 3, 3 -amino acid thioester with excellent selectivity (dr > 98 : 2). Syntheses of (+)-AG-041R and 3-aminopyrroloindoline have been accomplished utilizing the developed method.